A Thunderstorm Identification Method Combining the Area of Graupel Distribution Region and Weather Radar Reflectivity. Issue 1 (7th January 2020) - Yang, B.; Gao, X.; Han, Y.; Zhang, Y.; Gao, T.
Abstract: Thunderstorm identification from weather radar data remains a fundamental problem in lightning nowcasting. In this study, a novel thunderstorm identification method combining the area of graupel distribution region and weather radar reflectivity is proposed. To optimize identification parameters of the identification method, the radar echoes with 312 thunderstorms in 17 weather processes in Nanjing area, China, from 2014 to 2015 were identified and tested to obtain the optimal identification parameters. The results indicate that the optimal parameter combination is to set the storm region identification reflectivity threshold at 0°C isothermal level to 30 dBZ and set the area of graupel distribution region to 2 km 2 . With such a parameter combination, the optimal identification results with the probability of detection of 91%, false alarm rate of 6.9%, and critical success index of 85.3% could be obtained. Moreover, the proposed thunderstorm identification method can also provide effective means for thunderstorm nowcasting. Plain Language Summary: Thunderstorm is a kind of disastrous weather that often brings us great losses. If thunderstorms can be timely detected, we can take appropriate means to deal with them. Weather radar is considered as an efficient tool for detecting thunderstorms. It is an important problem in the application of weather radar to identify thunderstorms from radar echoes. In the present study, a new method for identifying thunderstorms using dual‐polarization weather radar is proposed, which combines reflectivity with the integral area of graupel related to thunderstorm electrification to identify thunderstorms. The method is tested by 312 thunderstorms in 17 weather processes in Nanjing area, China, from 2014 to 2015. The test results show that the method has good thunderstorm identification performance. Key Points: A novel thunderstorm identification method combining the area of graupel distribution region and weather radar reflectivity is proposed The area of graupel distribution region at certain isothermal levels is the key parameter of the thunderstorm identification method A detection probability of 91% and a false alarm rate of 6.9% can be achieved by the proposed method